2021
DOI: 10.1113/jp278810
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Warburg effect: historical dogma versus current understanding

Abstract: Contrary to Warburg's original thesis, accelerated aerobic glycolysis is not a primary, permanent and universal consequence of dysfunctional or impaired mitochondria compensating for poor ATP yield per mole of glucose. Instead, in most tumours the Warburg effect is an essential part of a ‘selfish’ metabolic reprogramming, which results from the interplay between (normoxic/hypoxic) hypoxia‐inducible factor‐1 (HIF‐1) overexpression, oncogene activation (cMyc, Ras), loss of function of tumour suppressors (mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
389
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 523 publications
(406 citation statements)
references
References 98 publications
(152 reference statements)
16
389
0
1
Order By: Relevance
“…This is a remarkable characteristic of cancer cells and has recently been applied as a method of detecting cancer by exploiting the characteristic of excessive glucose utilization by cancer cells [5]. It is essential to consider that cancer cells complete the glycolysis process regardless of absence or presence of oxygen [6]. When cancer cells only obtain glycolysis-dependent energy even in the presence of oxygen, the effect is called the "Warburg effect" [7].…”
Section: Introductionmentioning
confidence: 99%
“…This is a remarkable characteristic of cancer cells and has recently been applied as a method of detecting cancer by exploiting the characteristic of excessive glucose utilization by cancer cells [5]. It is essential to consider that cancer cells complete the glycolysis process regardless of absence or presence of oxygen [6]. When cancer cells only obtain glycolysis-dependent energy even in the presence of oxygen, the effect is called the "Warburg effect" [7].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, research has shown that tumor metabolism is not a static function but rather an essential part of metabolic reprogramming based on necessary adaptations caused by external or internal cellular factors [ 57 ]. It has been shown for example that the interplay between hypoxia-inducible factor-1 (HIF-1) overexpression, HIF-1 cooperation with epigenetic mechanisms, oncogene activation (cMyc, Ras), loss of function of tumor suppressors (mutant p53, mutant PTEN, miRNAs and sirtuins with suppressor functions), activated (PI3K-Akt-mTORC1, Ras-Raf-MEK-ERK-cMyc, Jak-Stat3) or deactivated (LKB1-AMPK) signaling pathways, and components of the tumor microenvironment (such as cancer-associated-fibroblasts) are likely to influence the metabolic phenotype of a tumor cell [ 11 ]. To see if the metabolic reprogramming of OSCC cells leading to increased SUVmax value might be linked to dysfunctions in ETS proteins, we evaluated if mutations in mtDNA coding for ETS genes at a certain level of heteroplasmy could have effects on SUVmax values by alterations in energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…According to the original Warburg model, complex cellular processes including mutations in genes coding for ETS proteins lead to this metabolic switch [ 10 ]. Recent work has extended this model, indicating that not only ETS mutations but also an interplay between various cellular signaling processes and interaction with the tumor microenvironment can lead to this metabolic phenotype [ 11 ]. However, metabolic analyses of various tumor models suggest that a fully functional ETS is a prerequisite for the malignant behavior of many cancer types [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Glycolytic phenotype is an important part of the metabolic reprogramming of cancer cells and occurs at an early stage of oncogenesis, i.e., before the development of tissue hypoxia. The history and current knowledge of the mechanisms and consequences of the Warburg effect are presented in a recent excellent review [ 45 ]. On the other hand, the role of Insulin/IGF signaling in the acquisition of the Warburg metabolic phenotypes in colorectal cancer cells is still not fully described [ 33 ].…”
Section: Introductionmentioning
confidence: 99%